STUDENTS’ PERCEPTION ON DOING FORMATIVE ASSESSMENT IN QUIZIZZ FOR LEARNING ENGLISH GRAMMAR - Dea Meliana; Totoh Tauhidin Abas; Hilmansyah Saefullah (IKIP Siliwangi, 2023)
The process of assessment involves gathering and debating data from numerous and varied sources; it is completed when assessment outcomes are applied to improve subsequent learning. The purpose of the study to explore student’s perception of the use Quizizz as formative assessment tool in learning grammar based on researcher view and experience, this research also worth observing insights into beliefs and principles of the researcher in designing formative assessment and the ways of designed and applied in Quizizz for learning English Grammar. This research use a self-reflective inquiry research methods. The research subjects were 5 students of eleventh grade. Data was collected through observation, interview and documentation. The results revealed thatpositive perspectives toward the use of Quizizz as an assessment tool by the teacher for English teaching and learning. It can be seen from the students responses, from the five theme of perception, the theme are absorption of stimulus from external individual, understanding and assessment or evaluation, all of the indicators was get very positive perception of using Quizizz as formative assessment.